Communication as an Educational Skill in School Units of the 21st: Century: A Survey Research (Asian Education Studies, 2017)
Awareness about values of communication skills and the necessity for their cultivation brought them into foreground of educational field. Thus, they are qualified as a basic framework for the creation of modern democratic, intercultural and open schools to the world. Communication is recognized as a basic social skill by the program P21 Framework for the 21st Century Learning and by thousands of teachers and hundreds of schools in the US and many other countries. Since communication skills are related to many aspects of modern Greek educational situation, such as teaching, school administration, evaluation and development of good interpersonal relationships, the main purpose of this paper is the presentation of a survey research about communicative behavior of secondary education teachers and school heads, the depiction and enhancement of their communication style and the assessment of their views in regards to importance of communication skills in carrying out their professional role. Results of the research showed that teachers recognize to themselves very good communication skills, including advocate active listening, collaboration development ability and empathy.